Address to the Canadian Club of Montreal - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the World Bank Group, spoke about the vigorous partnership between Canada and the World Bank. He described at length the relationship between Canada and the Bank in terms of lending and the country's progress in various areas of economic development.